A novel filter for terrain mapping with laser rangefinders - Cang Ye; Borenstein, J. (IEEE transactions on robotics, 2004)
This paper introduces a novel filter for terrain mapping with a two-dimensional laser rangefinder. The filter, called the certainty-assisted spatial (CAS) filter, uses the physical constraints on motion continuity and spatial continuity to identify corrupted pixels and missing data in an elevation map. The filter removes the corrupted pixels, fills in the missing data, and leaves the uncorrupted pixels intact so as to preserve the details of a terrain map. Our extensive indoor and outdoor mapping experiments show the CAS filter's superior performance in erroneous data reduction and map detail preservation over conventional filters.